Is There Any Basis for Categorizing the Business Judgment Rule as a Presumption? - Jarusevičius, Justinas (Teisė, 2019)
This article analyzes whether there are grounds for the case law to categorize the business judgment rule as a presumption. The author presents the main criterions that cause the categorization of the legal norm as a presumption. In the context of the identified criterions of the presumption category, it is evaluated whether the business judgment rule matches such criterions.